Mouse Models and Online Resources for Functional Analysis of Osteoporosis Genome-Wide Association Studies - Maynard, Robert D.; Ackert-Bicknell, Cheryl L. (Frontiers in Endocrinology, 2019)
Osteoporosis is a complex genetic disease in which the number of loci associated with the bone mineral density, a clinical risk factor for fracture, has increased at an exponential rate in the last decade. The identification of the causative variants and candidate genes underlying these loci has not been able to keep pace with the rate of locus discovery. A large number of tools and data resources have been built around the use of the mouse as model of human genetic disease. Herein, we describe resources available for functional validation of human Genome Wide Association Study (GWAS) loci using mouse models. We specifically focus on large-scale phenotyping efforts focused on bone relevant phenotypes and repositories of genotype-phenotype data that exist for transgenic and mutant mice, which can be readily mined as a first step towards more targeted efforts designed to deeply characterize the role of a gene in bone biology.